ASUHAN KEPERAWATAN PADA TN. W DENGAN CHRONIC KIDNEY DISEASE STAGE V ON HD DENGAN RIWAYAT HIPERTENSI DI RUANG HEMODIALISA RS BHAYANGKARA TK. I R. SAID SUKANTO - Dewy Indarty Putry (2022)
Background : Chronic kidney disease is a gradual and permanent decrease in kidney function so that there is a buildup of sodium, fluid and other nitrogen waste in the blood. This can be due to heart problems, type one and two diabetes and uncontrolled hypertension. Objective : This study was conducted to obtain experience and a real picture in providing nursing care to chronic kidney disease patients by including assessment, nursing diagnosis, nursing plan, nursing implementation, and nursing evaluation. Method : The research design used is a descriptive method in the form of a case study in implementing chronic kidney disease stage v on HD nursing care at Bhayangkara Hospital Tk. I R. Said Sukanto. Data collection was carried out by means of interviews, observations and physical examinations as well as documentation studies. Result : The nursing problems obtained in the case are excess fluid volume associated with impaired regulatory mechanisms, ineffectiveness of breath patterns related to respiratory muscle fatigue, activity intolerance is related to an imbalance between supply and oxygen demand. After nursing procedures for 1 x 5 hours, the results of the evaluation of one diagnosis are resolved, one diagnosis is partially resolved and one diagnosis has not been resolved. Conclusion : It is hoped that subsequent researchers can carry out nursing care in chronic kidney disease patients properly and appropriately so that they are achieved in accordance with the problems found in patients. Keywords : Nursing Care, Chronic Kidney Disease, Hypertension